High Risk Of Gestational Hypertension And Preconception Care On Incidence Of Pregnancy Hypertension - Anggraeni, Novi; Kasiati; Dwi Prihartini, Sabrina (Jurnal Kesehatan - STIKes Prima Nusantara, 2026)
Background: Hypertension in pregnancy is known to contribute to a variety of serious complications leading to maternal death. According to the World Health Organization (WHO), every day about 80% of maternal deaths are caused by complications that arise during pregnancy, childbirth, and postpartum. It was also found that out of 10 pregnant women in Jaddih Village with a gestational age of ≥20 weeks there were 2 people who experienced pre-eclampsia in the previous pregnancy. A total of 30% had carried out laboratory tests such as blood and urine tests before pregnancy, 100% received TT catin, and 50% had received information about healthy nutrition, signs of a healthy pregnancy during a consultation with a midwife before planning a pregnancy. Given that the exact cause of preeclampsia is not yet fully known, prevention measures focus on avoiding risk factors and controlling determinants that can trigger this condition. Prevention and control of risk factors can be initiated by screening for high risk of pregnancy hypertension and preconception care with the target starting before marriage.. Purpose: The purpose of this study was to analyze the effect of high risk of pregnancy hypertension and preconception care on the incidence of pregnancy hypertension. Methods: This type of research is observational with a cross sectional study design. The research was conducted in Jaddih Village, Bangkalan Regency April-May 2025. The sample in the study was 40 pregnant women. The sampling technique was accidental sampling. The instruments used were questionnaires and blood pressure gauges. Data analyzed by chi-square test. Results: Less than half of pregnant women are in the adequate preconception care category and more than half of pregnant women are not at high risk of gestational hypertension. Conclusion: High risk of pregnancy hypertension and preconception care influence the incidence of pregnancy hypertension